FLYPAPER EFFECT PADA PENGARUH DANA PERIMBANGAN, PENDAPATAN ASLI DAERAH DAN SISA LEBIH PEMBIAYAAN ANGGARAN TERHADAP BELANJA DAERAH (Studi Pada Kabupaten Lebak dan Pandeglang Provinsi Banten Periode 2014-2019) - Sefti Marici (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
This study aims to determine the flypaper effect on the effect of balancing fund, local revenue and financing surplus on regional expenditure in Lebak and Pandeglang Regencies Banten Province. The method of research analysis used in this research is descriptive method. The population and sample in this study were Lebak and Pandeglang Regencies Banten Province using the saturated sample method in the 2014-2019 period. The data used is secondary data collected by documentation technique. In analyzing the data, this study used a test tool of ordinary least square (OLS) analysis. The results of this research indicates that general allocation fund have a positive effect on regional expenditure, specific allocation fund have a positive effect on regional expenditure, profit-sharing fund have a positive effect on regional expenditure, local revenue does not have a positive effect on regional expenditure, financing surplus does not have a positive effect on regional expenditure and there has been a ſlypaper effect on regional expenditure. Keywords: Flypaper Effect, Balancing Fund, Local Revenue, Financing Surplus, Regional Expenditure